b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(a(a(c(c(x1)))))) → b(b(c(c(x1))))
a(a(d(d(x1)))) → d(d(c(c(x1))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(a(a(c(c(x1)))))) → b(b(c(c(x1))))
a(a(d(d(x1)))) → d(d(c(c(x1))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(a(a(c(c(x1)))))) → b(b(c(c(x1))))
a(a(d(d(x1)))) → d(d(c(c(x1))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x)))))) → b(b(d(d(c(c(x))))))
c(c(a(a(b(b(x)))))) → c(c(b(b(x))))
d(d(a(a(x)))) → c(c(d(d(x))))
b(b(b(b(b(b(x)))))) → c(c(b(b(a(a(x))))))
c(c(d(d(x)))) → d(d(b(b(x))))
c(c(d(d(x)))) → d(d(b(b(d(d(x))))))
c(c(a(a(d(d(x)))))) → b(b(b(b(x))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ RRRPoloQTRSProof
b(b(d(d(b(b(x)))))) → b(b(d(d(c(c(x))))))
c(c(a(a(b(b(x)))))) → c(c(b(b(x))))
d(d(a(a(x)))) → c(c(d(d(x))))
b(b(b(b(b(b(x)))))) → c(c(b(b(a(a(x))))))
c(c(d(d(x)))) → d(d(b(b(x))))
c(c(d(d(x)))) → d(d(b(b(d(d(x))))))
c(c(a(a(d(d(x)))))) → b(b(b(b(x))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(a(a(c(c(x1)))))) → b(b(c(c(x1))))
a(a(d(d(x1)))) → d(d(c(c(x1))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x)))))) → b(b(d(d(c(c(x))))))
c(c(a(a(b(b(x)))))) → c(c(b(b(x))))
d(d(a(a(x)))) → c(c(d(d(x))))
b(b(b(b(b(b(x)))))) → c(c(b(b(a(a(x))))))
c(c(d(d(x)))) → d(d(b(b(x))))
c(c(d(d(x)))) → d(d(b(b(d(d(x))))))
c(c(a(a(d(d(x)))))) → b(b(b(b(x))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
↳ RRRPoloQTRSProof
b(b(d(d(b(b(x)))))) → b(b(d(d(c(c(x))))))
c(c(a(a(b(b(x)))))) → c(c(b(b(x))))
d(d(a(a(x)))) → c(c(d(d(x))))
b(b(b(b(b(b(x)))))) → c(c(b(b(a(a(x))))))
c(c(d(d(x)))) → d(d(b(b(x))))
c(c(d(d(x)))) → d(d(b(b(d(d(x))))))
c(c(a(a(d(d(x)))))) → b(b(b(b(x))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(a(a(c(c(x1)))))) → b(b(c(c(x1))))
a(a(d(d(x1)))) → d(d(c(c(x1))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
Used ordering:
b(b(a(a(c(c(x1)))))) → b(b(c(c(x1))))
POL(a(x1)) = 2 + 2·x1
POL(b(x1)) = 2 + 2·x1
POL(c(x1)) = 2 + 2·x1
POL(d(x1)) = x1
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
a(a(d(d(x1)))) → d(d(c(c(x1))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
B(b(b(b(b(b(x1)))))) → A(a(b(b(c(c(x1))))))
D(d(a(a(c(c(x1)))))) → B(b(b(b(x1))))
A(a(d(d(x1)))) → D(c(c(x1)))
D(d(a(a(c(c(x1)))))) → B(b(b(x1)))
D(d(a(a(c(c(x1)))))) → B(b(x1))
D(d(c(c(x1)))) → D(b(b(d(d(x1)))))
D(d(a(a(c(c(x1)))))) → B(x1)
B(b(b(b(b(b(x1)))))) → A(b(b(c(c(x1)))))
D(d(c(c(x1)))) → D(d(x1))
B(b(b(b(b(b(x1)))))) → B(b(c(c(x1))))
B(b(b(b(b(b(x1)))))) → B(c(c(x1)))
D(d(c(c(x1)))) → B(d(d(x1)))
A(a(d(d(x1)))) → D(d(c(c(x1))))
D(d(c(c(x1)))) → B(b(d(d(x1))))
D(d(c(c(x1)))) → D(d(b(b(d(d(x1))))))
D(d(c(c(x1)))) → D(x1)
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
a(a(d(d(x1)))) → d(d(c(c(x1))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
B(b(b(b(b(b(x1)))))) → A(a(b(b(c(c(x1))))))
D(d(a(a(c(c(x1)))))) → B(b(b(b(x1))))
A(a(d(d(x1)))) → D(c(c(x1)))
D(d(a(a(c(c(x1)))))) → B(b(b(x1)))
D(d(a(a(c(c(x1)))))) → B(b(x1))
D(d(c(c(x1)))) → D(b(b(d(d(x1)))))
D(d(a(a(c(c(x1)))))) → B(x1)
B(b(b(b(b(b(x1)))))) → A(b(b(c(c(x1)))))
D(d(c(c(x1)))) → D(d(x1))
B(b(b(b(b(b(x1)))))) → B(b(c(c(x1))))
B(b(b(b(b(b(x1)))))) → B(c(c(x1)))
D(d(c(c(x1)))) → B(d(d(x1)))
A(a(d(d(x1)))) → D(d(c(c(x1))))
D(d(c(c(x1)))) → B(b(d(d(x1))))
D(d(c(c(x1)))) → D(d(b(b(d(d(x1))))))
D(d(c(c(x1)))) → D(x1)
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
a(a(d(d(x1)))) → d(d(c(c(x1))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ UsableRulesProof
D(d(c(c(x1)))) → D(d(x1))
D(d(c(c(x1)))) → D(b(b(d(d(x1)))))
D(d(c(c(x1)))) → D(d(b(b(d(d(x1))))))
D(d(c(c(x1)))) → D(x1)
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
a(a(d(d(x1)))) → d(d(c(c(x1))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ UsableRulesProof
D(d(c(c(x1)))) → D(d(x1))
D(d(c(c(x1)))) → D(b(b(d(d(x1)))))
D(d(c(c(x1)))) → D(d(b(b(d(d(x1))))))
D(d(c(c(x1)))) → D(x1)
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
D(d(c(c(x1)))) → D(d(x1))
D(d(c(c(x1)))) → D(x1)
POL(D(x1)) = x1
POL(a(x1)) = 1 + 2·x1
POL(b(x1)) = 1 + 2·x1
POL(c(x1)) = 1 + 2·x1
POL(d(x1)) = x1
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ UsableRulesProof
D(d(c(c(x1)))) → D(b(b(d(d(x1)))))
D(d(c(c(x1)))) → D(d(b(b(d(d(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
D(d(c(c(x1)))) → D(b(b(d(d(x1)))))
Used ordering: Polynomial Order [21,25] with Interpretation:
D(d(c(c(x1)))) → D(d(b(b(d(d(x1))))))
POL( c(x1) ) = max{0, -1}
POL( d(x1) ) = 1
POL( b(x1) ) = max{0, -1}
POL( D(x1) ) = x1 + 1
POL( a(x1) ) = max{0, -1}
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ UsableRulesProof
D(d(c(c(x1)))) → D(d(b(b(d(d(x1))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(b(b(d(d(x0)))))))))
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(d(d(b(b(d(d(x0)))))))))))
D(d(c(c(b(b(x0)))))) → D(d(c(c(d(d(b(b(x0))))))))
D(d(c(c(a(a(c(c(x0)))))))) → D(d(b(b(b(b(b(b(x0))))))))
D(d(c(c(d(a(a(c(c(x0))))))))) → D(d(b(b(d(b(b(b(b(x0)))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(d(d(b(b(d(d(x0))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(b(b(d(d(x0))))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ UsableRulesProof
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(b(b(d(d(x0)))))))))
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(d(d(b(b(d(d(x0)))))))))))
D(d(c(c(b(b(x0)))))) → D(d(c(c(d(d(b(b(x0))))))))
D(d(c(c(d(a(a(c(c(x0))))))))) → D(d(b(b(d(b(b(b(b(x0)))))))))
D(d(c(c(a(a(c(c(x0)))))))) → D(d(b(b(b(b(b(b(x0))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(d(d(b(b(d(d(x0))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(b(b(d(d(x0))))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
D(d(c(c(a(a(c(c(b(b(b(b(b(x0))))))))))))) → D(d(b(b(b(b(b(a(a(b(b(c(c(x0)))))))))))))
D(d(c(c(a(a(c(c(b(b(b(x0))))))))))) → D(d(b(b(b(a(a(b(b(c(c(x0)))))))))))
D(d(c(c(a(a(c(c(b(d(d(b(b(x0))))))))))))) → D(d(b(b(b(b(b(c(c(d(d(b(b(x0)))))))))))))
D(d(c(c(a(a(c(c(b(x0))))))))) → D(d(b(a(a(b(b(c(c(x0)))))))))
D(d(c(c(a(a(c(c(b(b(b(b(x0)))))))))))) → D(d(b(b(b(b(a(a(b(b(c(c(x0))))))))))))
D(d(c(c(a(a(c(c(d(d(b(b(x0)))))))))))) → D(d(b(b(b(b(c(c(d(d(b(b(x0))))))))))))
D(d(c(c(a(a(c(c(x0)))))))) → D(d(a(a(b(b(c(c(x0))))))))
D(d(c(c(a(a(c(c(b(b(x0)))))))))) → D(d(b(b(a(a(b(b(c(c(x0))))))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ UsableRulesProof
D(d(c(c(a(a(c(c(b(b(b(x0))))))))))) → D(d(b(b(b(a(a(b(b(c(c(x0)))))))))))
D(d(c(c(a(a(c(c(b(d(d(b(b(x0))))))))))))) → D(d(b(b(b(b(b(c(c(d(d(b(b(x0)))))))))))))
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(d(d(b(b(d(d(x0)))))))))))
D(d(c(c(a(a(c(c(b(x0))))))))) → D(d(b(a(a(b(b(c(c(x0)))))))))
D(d(c(c(b(b(x0)))))) → D(d(c(c(d(d(b(b(x0))))))))
D(d(c(c(a(a(c(c(x0)))))))) → D(d(a(a(b(b(c(c(x0))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(d(d(b(b(d(d(x0))))))))))
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(b(b(d(d(x0)))))))))
D(d(c(c(a(a(c(c(b(b(b(b(b(x0))))))))))))) → D(d(b(b(b(b(b(a(a(b(b(c(c(x0)))))))))))))
D(d(c(c(a(a(c(c(b(b(b(b(x0)))))))))))) → D(d(b(b(b(b(a(a(b(b(c(c(x0))))))))))))
D(d(c(c(d(a(a(c(c(x0))))))))) → D(d(b(b(d(b(b(b(b(x0)))))))))
D(d(c(c(a(a(c(c(d(d(b(b(x0)))))))))))) → D(d(b(b(b(b(c(c(d(d(b(b(x0))))))))))))
D(d(c(c(a(a(c(c(b(b(x0)))))))))) → D(d(b(b(a(a(b(b(c(c(x0))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(b(b(d(d(x0))))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ UsableRulesProof
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(b(b(d(d(x0)))))))))
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(d(d(b(b(d(d(x0)))))))))))
D(d(c(c(b(b(x0)))))) → D(d(c(c(d(d(b(b(x0))))))))
D(d(c(c(d(a(a(c(c(x0))))))))) → D(d(b(b(d(b(b(b(b(x0)))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(d(d(b(b(d(d(x0))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(b(b(d(d(x0))))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
D(d(c(c(d(a(a(c(c(b(b(x0))))))))))) → D(d(b(b(d(a(a(b(b(c(c(x0)))))))))))
D(d(c(c(d(a(a(c(c(b(d(d(b(b(x0)))))))))))))) → D(d(b(b(d(b(b(b(c(c(d(d(b(b(x0))))))))))))))
D(d(c(c(d(a(a(c(c(d(d(b(b(x0))))))))))))) → D(d(b(b(d(b(b(c(c(d(d(b(b(x0)))))))))))))
D(d(c(c(d(a(a(c(c(b(b(b(x0)))))))))))) → D(d(b(b(d(b(a(a(b(b(c(c(x0))))))))))))
D(d(c(c(d(a(a(c(c(b(b(b(b(b(x0)))))))))))))) → D(d(b(b(d(b(b(b(a(a(b(b(c(c(x0))))))))))))))
D(d(c(c(d(a(a(c(c(b(b(b(b(x0))))))))))))) → D(d(b(b(d(b(b(a(a(b(b(c(c(x0)))))))))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ UsableRulesProof
D(d(c(c(d(a(a(c(c(d(d(b(b(x0))))))))))))) → D(d(b(b(d(b(b(c(c(d(d(b(b(x0)))))))))))))
D(d(c(c(d(a(a(c(c(b(d(d(b(b(x0)))))))))))))) → D(d(b(b(d(b(b(b(c(c(d(d(b(b(x0))))))))))))))
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(b(b(d(d(x0)))))))))
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(d(d(b(b(d(d(x0)))))))))))
D(d(c(c(d(a(a(c(c(b(b(b(b(b(x0)))))))))))))) → D(d(b(b(d(b(b(b(a(a(b(b(c(c(x0))))))))))))))
D(d(c(c(b(b(x0)))))) → D(d(c(c(d(d(b(b(x0))))))))
D(d(c(c(d(a(a(c(c(b(b(b(b(x0))))))))))))) → D(d(b(b(d(b(b(a(a(b(b(c(c(x0)))))))))))))
D(d(c(c(d(a(a(c(c(b(b(x0))))))))))) → D(d(b(b(d(a(a(b(b(c(c(x0)))))))))))
D(d(c(c(d(a(a(c(c(b(b(b(x0)))))))))))) → D(d(b(b(d(b(a(a(b(b(c(c(x0))))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(d(d(b(b(d(d(x0))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(b(b(d(d(x0))))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ UsableRulesProof
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(b(b(d(d(x0)))))))))
D(d(c(c(d(c(c(x0))))))) → D(d(b(b(d(d(d(b(b(d(d(x0)))))))))))
D(d(c(c(b(b(x0)))))) → D(d(c(c(d(d(b(b(x0))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(d(d(b(b(d(d(x0))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(b(b(d(d(x0))))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
D.1(d.0(c.0(c.1(d.0(c.0(c.0(x0))))))) → D.1(d.0(b.0(b.1(d.0(b.0(b.0(d.1(d.0(x0)))))))))
D.1(d.0(c.0(c.0(c.0(c.1(x0)))))) → D.1(d.0(b.0(b.0(d.1(d.0(b.0(b.1(d.0(d.1(x0))))))))))
D.1(d.0(c.0(c.0(b.0(b.1(x0)))))) → D.1(d.0(c.0(c.0(d.1(d.0(b.0(b.1(x0))))))))
D.1(d.0(c.0(c.0(c.0(c.0(x0)))))) → D.1(d.0(b.0(b.0(d.1(d.0(b.0(b.0(d.1(d.0(x0))))))))))
D.1(d.0(c.0(c.1(d.0(c.0(c.0(x0))))))) → D.1(d.0(b.0(b.1(d.0(d.1(d.0(b.0(b.0(d.1(d.0(x0)))))))))))
D.1(d.0(c.0(c.0(b.0(b.0(x0)))))) → D.1(d.0(c.0(c.0(d.1(d.0(b.0(b.0(x0))))))))
D.1(d.0(c.0(c.1(d.0(c.0(c.1(x0))))))) → D.1(d.0(b.0(b.1(d.0(d.1(d.0(b.0(b.1(d.0(d.1(x0)))))))))))
D.1(d.0(c.0(c.0(c.0(c.0(x0)))))) → D.1(d.0(b.0(b.0(b.0(b.0(d.1(d.0(x0))))))))
D.1(d.0(c.0(c.1(d.0(c.0(c.1(x0))))))) → D.1(d.0(b.0(b.1(d.0(b.0(b.1(d.0(d.1(x0)))))))))
D.1(d.0(c.0(c.0(c.0(c.1(x0)))))) → D.1(d.0(b.0(b.0(b.0(b.1(d.0(d.1(x0))))))))
b.0(b.0(b.0(b.0(b.0(b.0(x1)))))) → a.0(a.0(b.0(b.0(c.0(c.0(x1))))))
b.0(b.0(d.1(d.0(b.0(b.0(x1)))))) → c.0(c.0(d.1(d.0(b.0(b.0(x1))))))
d.1(d.0(a.0(a.0(c.0(c.0(x1)))))) → b.0(b.0(b.0(b.0(x1))))
d.1(d.0(c.0(c.1(x1)))) → b.0(b.1(d.0(d.1(x1))))
b.0(b.0(d.1(d.0(b.0(b.1(x1)))))) → c.0(c.0(d.1(d.0(b.0(b.1(x1))))))
d.1(d.0(a.0(a.0(c.0(c.1(x1)))))) → b.0(b.0(b.0(b.1(x1))))
d.1(d.0(c.0(c.1(x1)))) → d.1(d.0(b.0(b.1(d.0(d.1(x1))))))
d.1(d.0(c.0(c.0(x1)))) → b.0(b.0(d.1(d.0(x1))))
b.0(b.0(b.0(b.0(b.0(b.1(x1)))))) → a.0(a.0(b.0(b.0(c.0(c.1(x1))))))
d.1(d.0(c.0(c.0(x1)))) → d.1(d.0(b.0(b.0(d.1(d.0(x1))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ SemLabProof2
↳ UsableRulesProof
D.1(d.0(c.0(c.1(d.0(c.0(c.0(x0))))))) → D.1(d.0(b.0(b.1(d.0(b.0(b.0(d.1(d.0(x0)))))))))
D.1(d.0(c.0(c.0(c.0(c.1(x0)))))) → D.1(d.0(b.0(b.0(d.1(d.0(b.0(b.1(d.0(d.1(x0))))))))))
D.1(d.0(c.0(c.0(b.0(b.1(x0)))))) → D.1(d.0(c.0(c.0(d.1(d.0(b.0(b.1(x0))))))))
D.1(d.0(c.0(c.0(c.0(c.0(x0)))))) → D.1(d.0(b.0(b.0(d.1(d.0(b.0(b.0(d.1(d.0(x0))))))))))
D.1(d.0(c.0(c.1(d.0(c.0(c.0(x0))))))) → D.1(d.0(b.0(b.1(d.0(d.1(d.0(b.0(b.0(d.1(d.0(x0)))))))))))
D.1(d.0(c.0(c.0(b.0(b.0(x0)))))) → D.1(d.0(c.0(c.0(d.1(d.0(b.0(b.0(x0))))))))
D.1(d.0(c.0(c.1(d.0(c.0(c.1(x0))))))) → D.1(d.0(b.0(b.1(d.0(d.1(d.0(b.0(b.1(d.0(d.1(x0)))))))))))
D.1(d.0(c.0(c.0(c.0(c.0(x0)))))) → D.1(d.0(b.0(b.0(b.0(b.0(d.1(d.0(x0))))))))
D.1(d.0(c.0(c.1(d.0(c.0(c.1(x0))))))) → D.1(d.0(b.0(b.1(d.0(b.0(b.1(d.0(d.1(x0)))))))))
D.1(d.0(c.0(c.0(c.0(c.1(x0)))))) → D.1(d.0(b.0(b.0(b.0(b.1(d.0(d.1(x0))))))))
b.0(b.0(b.0(b.0(b.0(b.0(x1)))))) → a.0(a.0(b.0(b.0(c.0(c.0(x1))))))
b.0(b.0(d.1(d.0(b.0(b.0(x1)))))) → c.0(c.0(d.1(d.0(b.0(b.0(x1))))))
d.1(d.0(a.0(a.0(c.0(c.0(x1)))))) → b.0(b.0(b.0(b.0(x1))))
d.1(d.0(c.0(c.1(x1)))) → b.0(b.1(d.0(d.1(x1))))
b.0(b.0(d.1(d.0(b.0(b.1(x1)))))) → c.0(c.0(d.1(d.0(b.0(b.1(x1))))))
d.1(d.0(a.0(a.0(c.0(c.1(x1)))))) → b.0(b.0(b.0(b.1(x1))))
d.1(d.0(c.0(c.1(x1)))) → d.1(d.0(b.0(b.1(d.0(d.1(x1))))))
d.1(d.0(c.0(c.0(x1)))) → b.0(b.0(d.1(d.0(x1))))
b.0(b.0(b.0(b.0(b.0(b.1(x1)))))) → a.0(a.0(b.0(b.0(c.0(c.1(x1))))))
d.1(d.0(c.0(c.0(x1)))) → d.1(d.0(b.0(b.0(d.1(d.0(x1))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof2
↳ UsableRulesProof
D.1(d.0(c.0(c.0(c.0(c.0(x0)))))) → D.1(d.0(b.0(b.0(d.1(d.0(b.0(b.0(d.1(d.0(x0))))))))))
D.1(d.0(c.0(c.0(b.0(b.0(x0)))))) → D.1(d.0(c.0(c.0(d.1(d.0(b.0(b.0(x0))))))))
D.1(d.0(c.0(c.0(c.0(c.0(x0)))))) → D.1(d.0(b.0(b.0(b.0(b.0(d.1(d.0(x0))))))))
b.0(b.0(b.0(b.0(b.0(b.0(x1)))))) → a.0(a.0(b.0(b.0(c.0(c.0(x1))))))
b.0(b.0(d.1(d.0(b.0(b.0(x1)))))) → c.0(c.0(d.1(d.0(b.0(b.0(x1))))))
d.1(d.0(a.0(a.0(c.0(c.0(x1)))))) → b.0(b.0(b.0(b.0(x1))))
d.1(d.0(c.0(c.1(x1)))) → b.0(b.1(d.0(d.1(x1))))
b.0(b.0(d.1(d.0(b.0(b.1(x1)))))) → c.0(c.0(d.1(d.0(b.0(b.1(x1))))))
d.1(d.0(a.0(a.0(c.0(c.1(x1)))))) → b.0(b.0(b.0(b.1(x1))))
d.1(d.0(c.0(c.1(x1)))) → d.1(d.0(b.0(b.1(d.0(d.1(x1))))))
d.1(d.0(c.0(c.0(x1)))) → b.0(b.0(d.1(d.0(x1))))
b.0(b.0(b.0(b.0(b.0(b.1(x1)))))) → a.0(a.0(b.0(b.0(c.0(c.1(x1))))))
d.1(d.0(c.0(c.0(x1)))) → d.1(d.0(b.0(b.0(d.1(d.0(x1))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ UsableRulesProof
D(d(c(c(b(b(x0)))))) → D(d(c(c(d(d(b(b(x0))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(d(d(b(b(d(d(x0))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(b(b(d(d(x0))))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ UsableRulesProof
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
D(d(c(c(b(b(x0)))))) → D(d(c(c(d(d(b(b(x0))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(d(d(b(b(d(d(x0))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(b(b(d(d(x0))))))))
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))
D(d(c(c(b(b(x0)))))) → D(d(c(c(d(d(b(b(x0))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(d(d(b(b(d(d(x0))))))))))
D(d(c(c(c(c(x0)))))) → D(d(b(b(b(b(d(d(x0))))))))
c(c(d(d(x)))) → d(d(b(b(x))))
c(c(d(d(x)))) → d(d(b(b(d(d(x))))))
c(c(a(a(d(d(x)))))) → b(b(b(b(x))))
b(b(d(d(b(b(x)))))) → b(b(d(d(c(c(x))))))
b(b(b(b(b(b(x)))))) → c(c(b(b(a(a(x))))))
b(b(c(c(d(D(x)))))) → b(b(d(d(c(c(d(D(x))))))))
c(c(c(c(d(D(x)))))) → d(d(b(b(d(d(b(b(d(D(x))))))))))
c(c(c(c(d(D(x)))))) → d(d(b(b(b(b(d(D(x))))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ RFCMatchBoundsTRSProof
↳ UsableRulesProof
c(c(d(d(x)))) → d(d(b(b(x))))
c(c(d(d(x)))) → d(d(b(b(d(d(x))))))
c(c(a(a(d(d(x)))))) → b(b(b(b(x))))
b(b(d(d(b(b(x)))))) → b(b(d(d(c(c(x))))))
b(b(b(b(b(b(x)))))) → c(c(b(b(a(a(x))))))
b(b(c(c(d(D(x)))))) → b(b(d(d(c(c(d(D(x))))))))
c(c(c(c(d(D(x)))))) → d(d(b(b(d(d(b(b(d(D(x))))))))))
c(c(c(c(d(D(x)))))) → d(d(b(b(b(b(d(D(x))))))))
c(c(d(d(x)))) → d(d(b(b(x))))
c(c(d(d(x)))) → d(d(b(b(d(d(x))))))
c(c(a(a(d(d(x)))))) → b(b(b(b(x))))
b(b(d(d(b(b(x)))))) → b(b(d(d(c(c(x))))))
b(b(b(b(b(b(x)))))) → c(c(b(b(a(a(x))))))
b(b(c(c(d(D(x)))))) → b(b(d(d(c(c(d(D(x))))))))
c(c(c(c(d(D(x)))))) → d(d(b(b(d(d(b(b(d(D(x))))))))))
c(c(c(c(d(D(x)))))) → d(d(b(b(b(b(d(D(x))))))))
The certificate consists of the following enumerated nodes:
5680, 5681, 5686, 5685, 5684, 5683, 5682, 5693, 5694, 5692, 5689, 5690, 5688, 5695, 5691, 5687, 5696, 5697, 5698, 5699, 5700, 5705, 5706, 5704, 5703, 5702, 5707, 5701, 5708, 5709, 5714, 5713, 5710, 5711, 5712, 5717, 5716, 5715, 5722, 5721, 5720, 5719, 5718, 5723, 5724, 5725, 5726, 5727, 5728, 5729, 5734, 5733, 5730, 5731, 5732, 5741, 5742, 5740, 5737, 5738, 5736, 5743, 5739, 5735, 5751, 5752, 5750, 5749, 5748, 5753, 5747, 5756, 5755, 5754, 5762, 5763, 5766, 5765, 5764, 5767, 5768, 5769, 5770, 5771, 5772, 5773, 5776, 5775, 5774
Node 5680 is start node and node 5681 is final node.
Those nodes are connect through the following edges:
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ UsableRulesProof
↳ QDP
D(d(c(c(x1)))) → D(d(x1))
D(d(c(c(x1)))) → D(b(b(d(d(x1)))))
D(d(c(c(x1)))) → D(d(b(b(d(d(x1))))))
D(d(c(c(x1)))) → D(x1)
d(d(c(c(x1)))) → b(b(d(d(x1))))
d(d(c(c(x1)))) → d(d(b(b(d(d(x1))))))
d(d(a(a(c(c(x1)))))) → b(b(b(b(x1))))
b(b(d(d(b(b(x1)))))) → c(c(d(d(b(b(x1))))))
b(b(b(b(b(b(x1)))))) → a(a(b(b(c(c(x1))))))